Evolutionary overview of biofuels productivity in Brazil in the last 10 years - Reis, Marcelo Cardoso dos; Gonçalves, Wellington; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2022)
The decrease in reserves of fossil fuels, such as oil, combined with price fluctuations and the evidence for the preservation of the environment, highlight the need to diversify the global energy matrix through the use of renewable fuels. Biofuels, especially Ethanol and Biodiesel B100, according to the literature, can be considered an adequate alternative to mitigate a fraction of pollutant emissions. Thus, an analysis of the national production of these biofuels is necessary to understand the periods of rise and decline of production, as well as their connection with consumption and government incentives to maintain production incentive programs in operation. Within this context, an overview of production was carried out based on data from the National Agency for Petroleum, Natural Gas and Biofuels through the use of the GraphPad Prism 9 software. As main results, it was verified that several studies point to gaps in government planning, financial and climate crises, in addition to significant changes in investments by important companies in the sector, which culminated in the deactivation of plants.
Keywords: Renewable energy; Alternative biofuels; Environment; Land use; Production